2010
DOI: 10.1080/02626660903529049
|View full text |Cite
|
Sign up to set email alerts
|

Spatial soil loss risk and reservoir siltation in semi-arid Tunisia

Abstract: Soil erosion vulnerability and extreme rainfall characteristics over the Mediterranean semi-arid region of Tunisia are crucial input for estimation of siltation rate in artificial reservoirs. A comprehensive high resolution database on erosive rainfall, together with siltation records for 28 small reservoirs, were analysed for this region, the Tunisian Dorsal (the easternmost part of the Atlas Mountains). The general life-span of these reservoirs is only about 14 years. Depending on the soil degradation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 23 publications
1
29
1
2
Order By: Relevance
“…Nevertheless, some crops are more prone to soil erosion than others. There is a paucity of quantitative information on soil erosion under various crops in the Mediterranean, but the available data confirm that cereal cultivation can be affected by rilling and gullying, even on smooth gradients (Casalí et al, 1999;Kosmas et al, 2002), with increasing soil loss as mean precipitation increases (Kosmas et al, 1997;Jebari et al, 2010). In cereal cultivation the soil is bare during autumn and part of winter, which coincides with one of the rainiest periods in the Mediterranean region and the season having the most intense rainstorms, particularly in the western Mediterranean.…”
Section: The Erosion Consequences Of Changing Agriculturementioning
confidence: 99%
“…Nevertheless, some crops are more prone to soil erosion than others. There is a paucity of quantitative information on soil erosion under various crops in the Mediterranean, but the available data confirm that cereal cultivation can be affected by rilling and gullying, even on smooth gradients (Casalí et al, 1999;Kosmas et al, 2002), with increasing soil loss as mean precipitation increases (Kosmas et al, 1997;Jebari et al, 2010). In cereal cultivation the soil is bare during autumn and part of winter, which coincides with one of the rainiest periods in the Mediterranean region and the season having the most intense rainstorms, particularly in the western Mediterranean.…”
Section: The Erosion Consequences Of Changing Agriculturementioning
confidence: 99%
“…Recent research has shown that semi-arid areas are very vulnerable to this phenomenon (e.g. GarciaRuiz et al 2010, Jebari et al 2010, Zucca et al 2010, Barbayiannis et al 2011. In fact, water erosion processes result in decrease in crop yields, loss in water potential, and are a cause of recurrent natural catastrophes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Much more diverse silting intensity is characteristic of small reservoirs in Tunisia. The data presented in the paper by Jebari et al [47] indicate that some of the reservoirs after ten years of operation are silted up 30%-40%, but among them there are some reservoirs whose silting degree is only a few percent. Among 23 reservoirs analyzed in the studies of Jebari et al [47], two of them were silted in ca.…”
Section: Siltation Ratementioning
confidence: 99%
“…The reservoir Krempna is located in a mountainous area with intensive surface erosion, and the catchment of the reservoir Zesławice, whereby 78% of the area is used for agricultural purposes, is covered with loess. It can be observed that a small reservoir becomes silted up faster if the siltation rate reaches 20% over a dozen years of operation (Table 3), in contrast to large reservoirs that achieve that level over centuries [46][47][48][49]. Krempna-1, Krempna-2, Zesławice, Głuchów reservoirs are characterized with such fast silting up, as well as Cierpisz reservoir in the period after its desilting and rebuilding i.e., from 1990 to present (Table 3).…”
Section: Siltation Ratementioning
confidence: 99%